Effects of Cobalt on Some Physiological Parameters of Common Bean (Phaselous vulgaris L.) - HALILOVA, H.; SOZUDOGRU OK, S.; TABAN, S. (Asian Journal of Chemistry, 2010)
A greenhouse experiment was carried out in an alkaline soil to study effects of cobalt on the nitrogen-reductase activity, total chlorophyll, nitrogen and cobalt contents of bean plant. The results showed that nitrogen-reductase enzyme activity increased at higher cobalt applications comparing to the control. Total chlorophyll content of the plants was affected by cobalt treatments statistically. As cobalt concentrations increased, total chlorophyll content of the plants decreased below the control. Dry weights of plants indicated that growth was increased at low cobalt concentrations, while was decreased as cobalt concentrations increased. Nitrogen content of the plants increased at 0.10 μg g-1 cobalt treatment and then decreased with the increasing applications.